Pollen record of early- to mid-Holocene vegetation and climate dynamics on the eastern coast of the Yellow Sea, South Korea. (June 2018) - Song, Bing; Yi, Sangheon; Nahm, Wook-Hyun; Lee, Jin-Young; Mao, Limi; Sha, Longbin; Yang, Zhongyong; Zhang, Jinpeng
To understand the early- to mid-Holocene vegetation and climate dynamics on the eastern coast of the Yellow Sea, we obtained a sedimentary core with high-resolution accelerator mass spectrometry (AMS) carbon 14 ( 14 C) data from the Gunsan coast in South Korea. The palynological analysis demonstrated that the riverine wetland meadow from 12.1 to 9.8 cal. kyr BP changed to temperate deciduous broad-leaved forest in 9.8–2.8 cal. kyr BP. In addition, the cold climate from 12.1 to 9.8 cal. kyr BP became warmer from 8.5 to 7.3 cal. kyr BP. This was followed by another relatively cold period from 7.3 to 2.8 cal. kyr BP. The temperature change was mainly in response to solar factors. However, there are two relatively humid periods from 12.1 to 9.8 and 8.5 to 7.3 cal. kyr BP, which arose for different reasons. The earlier humid period resulted from strong westerlies and a rapidly rising sea level. The later humid period was produced mainly by the strong East Asian summer monsoon (EASM) and may also be linked to La Niña–like activity. The cold 'Younger Dryas' event from 12.0 to 11.4 cal. kyr BP recorded in this study may have been produced by a North Atlantic meltwater pulse. This would have reduced temperatures that were already low because of weak insolation, and the strong winter monsoons would have increased the precipitation.